An INSULIN and IAPP dual reporter enables tracking of functional maturation of stem cell-derived insulin producing cells - Carmen L. Bayly; Xiao-Qing Dai; Cuilan Nian; Paul C. Orban; C. Bruce Verchere; Patrick E. MacDonald; Francis C. Lynn (Elsevier, 2024)
Objective: Human embryonic stem cell (hESC; SC)-derived pancreatic β cells can be used to study diabetes pathologies and develop cell replacement therapies. Although current differentiation protocols yield SCβ cells with varying degrees of maturation, these cells still differ from deceased donor human β cells in several respects. We sought to develop a reporter cell line that could be used to dynamically track SCβ cell functional maturation. Methods: To monitor SCβ cell maturation in vitro, we created an IAPP-2A-mScar and INSULIN-2A-EGFP dual fluorescent reporter (INS2A-EGFP/+;IAPP2A-mScarlet/+) hESC line using CRISPR/Cas9. Pluripotent SC were then differentiated using a 7-stage protocol to islet-like cells. Immunohistochemistry, flow cytometry, qPCR, GSIS and electrophysiology were used to characterise resulting cell populations. Results: We observed robust expression of EGFP and mScarlet fluorescent proteins in insulin- and IAPP-expressing cells without any compromise to their differentiation. We show that the proportion of insulin-producing cells expressing IAPP increases over a 4-week maturation period, and that a subset of insulin-expressing cells remain IAPP-free. Compared to this IAPP-free population, we show these insulin- and IAPP-expressing cells are less polyhormonal, more glucose-sensitive, and exhibit decreased action potential firing in low (2.8 mM) glucose. Conclusions: The INS2A-EGFP/+;IAPP2A-mScarlet/+ hESC line provides a useful tool for tracking populations of maturing hESC-derived β cells in vitro. This tool has already been shared with 3 groups and is freely available to all.